Contribution of digital books to online learning in lecturers and student perceptions - Cerianing Putri Pratiwi; Alfiati Alfiati (Universitas PGRI Madiun, 2023)
: A digital book is a book that is compiled, converted and published into a digital format. The purpose of this study is to describe lecturer and students' views on the contribution of digital books to learning. This research was included in the survey research, by conducting a survey of lecturer and students in Madiun City, with a sample of 7 lecturer and 102 students. Data collection techniques using closed questionnaires with indicators are a) Readiness of lecturers and students to use digital books, b) ease of use of digital books, c) the benefits of digital books in the learning process. The results of the analysis show that as many as lecturers and students are more likely to agree that digital books have a contribution to online learning. Lecturers and students stated that they were ready for online learning using digital books. Many lecturers and students operate digital books easily. Lecturer and students also stated that digital books have benefits, namely being more practical, easy to obtain, saving costs, increasing learning motivation, making it easier to learn independently, being able to provide new experiences in learning, making it easier for students to understand the material, having attractive features and appearance, making student achievement increase, being able to evaluate the learning process, learning with digital books can assess themselves.